LANGUAGE LEARNING STYLE IN MANAGEMENT STUDENTS FROM DIFFERENT GENDER GROUP - Daniatussalma Daniatussalma; Yudhi Arifani; Candra Hadi Asmara (Universitas Muhammadiyah Gresik, 2020)
Learning style is one factor which can determine students in the way how they obtained the learning or information. Between male and female students were different in choosing their learning styles. This study tried to investigate the perceptual learning styles preference in Management students and to know the differences between male and female Management students in learning styles in the first semester at University of Muhammadiyah Gresik. Perceptual Learning Style Preference Questionnaire (PLSPQ) developed by Reid 1987was used and administered to 230 students. An observation check-list also used to support the data with questionnaire. Descriptive Statistic was used to analyze the data. The result indicated that students preferred in Group style when they learned English as Academic Purpose (EAP). In gender, between female and male students showed there were some differences in their learning styles. The result revealed that female students preferred in Group style, meanwhile male students preferred in auditory style. The least preference of learning style both female and male students was Individual style